Roll, right, repeat: short-term repeatability in the self-righting behaviour of a cold-water sea cucumber. (13th February 2020) - Clements, Jeff C.; Schagerström, Ellen; Dupont, Sam; Jutfelt, Fredrik; Ramesh, Kirti
Abstract: For many benthic marine invertebrates, inversion (being turned upside-down) is a common event that can increase vulnerability to predation, desiccation and unwanted spatial transport, and requires behavioural 'self-righting' to correct. While self-righting behaviour has been studied for more than a century, the repeatability (R) – the portion of behavioural variance due to inter-individual differences – of this trait is not well understood. Heritability and the evolution of animal behaviour rely on behavioural repeatability. Here, we examined the self-righting technique of a cold-water holothurid, Parastichopus tremulus, and assessed the repeatability of this behaviour. Under laboratory conditions, P. tremulus consistently used muscle contractions to curl its body and roll itself back to an upright position, which provided for rapid ( x̅ ± SD = 96.7 ± 49.8 s) and highly repeatable ( R = 0.75) self-righting in the short term that varied between individuals (range of individual average righting times = 34.8–217.0 s). Righting time tended to increase with animal size; however, substantial variation was evident at comparable sizes, as average righting time ranged from 34.8–155.5 s for animals 20 cm in body length. Contrary to previous studies on other echinoderms, we found no evidence of improved righting times for P. tremulus over time. This study ultimately provides the first detailed documentation of self-righting behaviour for P. tremulus and suggests that this species displays a high degree of repeatability for this trait in the short term.